Correction of an anterior and posterior crossbite case with a modified McNamara appliance: A case report - Wendes Dias Mendes; Luciane Macedo de Menezes; Fábio Romano; Mírian Aiko Nakame Matsumoto; Maria Bernadete Sasso Stuani (Arbu Academic Publishing, 2021)
Anterior and posterior crossbites are malocclusions in the sagittal and transversal dimensions, respectively. As self-correction is rare in these alterations, early interception is recommended to allow normal occlusion and facial development. This case report aimed to discuss the treatment of an eight-year-old boy with an increased inferior facial third, who was submitted for rapid maxillary expansion with a modified bonded appliance to solve both transversal and anteroposterior deficiencies. The correctionof both malocclusions was achieved within 21 days. The advantages of this procedure were to gain space in both arches, enlarge the maxillary arch, and improve nasal breathing. The interceptive therapy, as well as a well-planned appliance, proved to be effective and important for retrieving the patient ́s normal condition and quality of life.